Controllable Radical Polymerization of Selenide Functionalized Vinyl Monomers and Its Application in Redox Responsive Photonic Crystals. Issue 18 (5th February 2021) - Liu, Shaoxiang; Li, Qilong; Li, Yingying; Zhang, Jiandong; Pan, Xiangqiang; Zhu, Jian; Zhu, Xiulin
Abstract: Selenium‐containing monomer ( p ‐phenylseleno) styrene ( p ‐PhSeSt) is polymerized by reversible addition‐fragmentation chain transfer polymerization. Polymer, (P( p ‐PhSeSt)), with controlled molecular weight and narrow molecular weight is obtained. The selenide moiety in obtained P( p ‐PhSeSt) can be selectively oxidized to selenoxide or selenone groups by H2 O2 or NaClO, respectively. These oxidized groups can be further reduced to selenide by Na2 S2 O4 . The structure changing of polymers during such redox cycle is characterized by nuclear magnetic resonance, X‐ray photoelectron spectroscopy, and size exclusion chromatography. Properties, such as thermal performance, glass transition temperature, water contact angles, and refractive indices, of the resulting polymers are systematically investigated before and after oxidation. In addition, SiO2 inverse opal photonic crystal (IOPC) is fabricated by sacrificial polymer colloidal template method. Owing to changes of the RIs of P( p ‐PhSeSt) after selective oxidation, the predictable change of PC bandgap as a redox‐responsive PC sensor is successfully realized, which provides new perspectives for modulating photonic crystals. Abstract : Novel selenide functionalized polymer with controlled structures is synthesized through reversible addition‐fragmentation chain transfer polymerization. Selenide group in obtained polymers can be selectively oxidized to selenoxide or selenone by H2 O2 or NaClO, respectively. Photonic crystal is fabricated using such polymer which offers the redox‐responsive behaviors.